COVID-19 Vaccine Acceptance among Health Care Providers in Rural Areas of Northern State, Sudan - Hamad, Nadia Ahmed Mohammed; Hamid, Amal Mohammed; Mohamed, Amal Abdelgadir; Sharaf, Khalida Hussain Saeed (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Aim: The present study assessed the adherence to the COVID-19 vaccine among healthcare providers in Rural Areas in the Northern State of Sudan. Background: Control of coronavirus disease (COVID-19) through vaccination is not merely dependent on vaccine efficacy and safety. Instead, the vaccine also needs to have health professionals and general public acceptance for successful control of the virus. Methodology: A descriptive cross-sectional study was conducted at Merowe Hospital in a rural area in the Northern state of Sudan; the hospital offers medical and health services for many villages around the hospital, and the study period was extended from December 2021 to March 2022. The study was carried out among 108 participants; they were selected using a purposive sampling technique. Data were collected via a questionnaire. Data was entered into SPSS version 25. Analysis was done using frequency tables and cross-tabulations; significance was considered at P \(\le\) 0.05. Results: The study found that 52.8% were not vaccinated, while 72.2% of total participants would recommend the COVID-19 vaccine to their family, friends, and patients, and 53.7% said that they had contributed to community campaigns to encourage people to get the vaccine,64.7% of vaccinated participants took the vaccine because they were afraid of occupational hazards, 27.8% their respond about vaccine effect in prevention was negative and there was a significant association between profession and contribution in community campaign P-value equal to 0.035. The finding indicates that the major obstacle to vaccination adherence and acceptance is a lack of reliable information, a challenge that authorities could address quickly. By providing comprehensive and accurate vaccine information, authorities could significantly improve vaccination adherence, acceptance, and coverage. Conclusion: Nearly half of the participants (47.2%) were immunized. Getting enough and correct information about the vaccines that the available was the main aspect that could enhance vaccination uptake. The current analysis offers the authorities profound insights into the anticipated challenges, issues, and potential courses of action. Efficient and evidence-based measures to encourage the use of the COVID-19 vaccine among healthcare providers are urgently required.